Pelaksanaan Desain Panggangan dan Meja Berjaring Ergonomis untuk Pekerja Pembuat Kemplang Di Desa Meranjat Ogan Ilir Sumatera Selatan - Andarini, Desheila; Waldani, Dina; Lestari, Mona; Fujianti, Poppy; Novrikasari, Novrikasari; Camelia, Anita (PT.Mantaya Idea Batara, 2025)
Kemplang cracker craftsmen in Ogan Ilir Regency are one of the businesses chosen by craftswomen, especially the kemplang cracker industry. Based on the phenomenon of the kemplang cracker home industry, there are now quite a lot of kemplang cracker home industries in the area and also for some people who make crackers, this business is the main livelihood and for women craftsmen it is an income to increase household income so that it becomes a cracker producing center kemplang in the Ogan Ilir area. Based on the urgency of this problem, an ergonomic chair has been created as a first step which has been adapted to the anthropometry of workers and trials have been carried out on kemplang grill workers and the results show that the chair used is able to reduce perceived MSDs complaints. Chairs are available and have been successfully implemented, but additional work tools need to be made in the form of iron net tables, which have been initially tested using the Posture Evaluation Index method in the Virtual Environment, which produces a score of 3, which means it is able to reduce the risk of MSDs in workers, so further service activities are needed in the form of implementing their use. ergonomic grill and mesh table designs for kemplang making workers in Meranjat Village, Ogan Ilir. The results of this Community Service Activity are that there are differences in the risk level of musculoskeletal complaints before and after the intervention. From the Pre-Test results, there were 9 people (39.1%) with a low risk level, 10 people (43.5%) with a medium risk level, and 4 people (17.4%) with a high risk level. Meanwhile, from the Post-Test results, there were 9 people (39.1%) with a low risk level, and 14 other people (60.9%) had a medium risk level Keywords : Grill Design, Net Table, Kemplang Worker